Sistem Penjualan Online Untuk Meningkatkan Usaha Mikro Kecil Menengah (UMKM) berbasis E-Marketplace - Riskha Yusepra; Lukman Hakim; Satrianansyah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Micro, small and medium enterprises (MSMEs) are companies established by individuals or companies that are not affiliated with a particular company and according to a predetermined category. UMKM itself is a form of corporation engaged in various business fields that affect the interests of society. With the development of global business and technology, it is no longer enough for companies to just rely on advertisements and brochures to promote their business. This requires many companies to change their existing business concepts and mechanisms to become more profitable. Many electronic marketplaces have sprung up, although the forms currently being taken by electronic marketplaces in Indonesia are mostly in the form of advertising. Where there is direct interaction between buyers and sellers, while the electronic marketplace provider only acts as a place of trade. To overcome the problems described above, the electronic market can be used as a solution to promote the products of cooperatives and micro, small and medium enterprises (MSMEs) in the city of Lubuklinggau. There is no online sales and ordering system for marketing products for micro, small and medium enterprises (MSMEs) in Lubuklinggau city, making it difficult for consumers outside the city to obtain information on product results for micro, small and medium enterprises Found large-scale companies (MSMEs) in the town of Lubuklinggau. E-Marketplace uses digital media in the form of the internet to create an environment or place where sellers and buyers carry out business processes, starting with product marketing, product delivery and developing communication between sellers and buyers so that both are satisfied.